Effects of Ce addition on microstructure, mechanical properties and corrosion resistance of as-cast AZ80 magnesium alloy - Wang Wei (China Foundry, 2014)
In this study, Ce was introduced into the AZ80 alloy and the effects of Ce addition on the microstructure, mechanical properties and corrosion resistance of the as-cast AZ80 magnesium alloy were investigated. The results show that the addition of Ce into the AZ80 alloy can not only refine the microstructure, but also result in the formation of the needle-like Al4Ce phase. These tiny Al4Ce phases are homogeneously distributed at grain boundaries and within grains. An appropriate Ce addition can also change the β-Mg17Al12 phase at the grain boundaries from continuous network to small island-like. At the same time, with the increase of Ce content from 0 to 2.0wt.%, the macro-hardness of the as-cast alloy is enhanced linearly, while impact toughness, tensile strength and elongation all firstly increase and then decrease. The AZ80 alloy containing 1.0wt.% Ce exhibits the optimal properties. Its macro-hardness, impact toughness, tensile strength and elongation are 61.90 HB, 15.50 J·cm-2, 171.80 MPa and 3.35%, increase by 9.95%, 63%, 13.3% and 36.7%, respectively compared with the base alloy. In addition, Ce can enhance the corrosion resistance of the AZ80 magnesium alloy.